Supporting individualised nursing care by leadership - Stolt, Minna; Charalambous, Andreas; Suhonen, Riitta A. (My University, 2018)
In recent years, individualised care has emerged as the golden standard for healthcare, one that has been promised by policymakers, is desired by patients and families, and has been championed by nurses and allied professionals in an increasing number of countries around the globe. Such demands pose challenges for healthcare management and leadership, especially nursing leadership. Individualised nursing care delivery has been found to be associated with some organisational variables including organisation of work, but especially leadership and management. Previous studies have shown that management and leadership are important factors in supporting the delivery of individualised care. The association of individualised nursing care and leadership goes beyond its supportive role and includes the cultivation of an appropriate patient-centred culture and environment where individualised care can be introduced. This chapter sheds light on the associations between individualised nursing care and leadership as well as presenting the pathway by which leadership can cultivate an individualised caring environment.
Keywords: Ethical issues; Individualised care; Leadership; Management; Nursing leaders